RANCANG BANGUN COMPANY PROFILE NADINE JAYA MEDIKA BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPING - Manurung, Rizky Ridwan; Erzi Hidayat (ABEC Indonesia, 2023)
Klinik Nadine Jaya Medika is located on Raja Ali Haji Street, Dumai Barat Subdistrict, Dumai City. Klinik Nadine Jaya Medika is a healthcare company that provides several health services, including General Clinic, Elderly Care Clinic, Non-Communicable Diseases Clinic, Pediatrics Clinic, Maternity Clinic, and Laboratory services. Currently, the dissemination and introduction of the clinic are still done conventionally. Challenges that have been encountered include limited information reach, restricted information availability, inefficient clinic information dissemination, and repetitive patient inquiries. To address these issues, this research aims to create a company profile website using the prototyping method. Prototyping is a software development method that allows interaction between the system developers and users, thereby overcoming any mismatches between them. Black box testing results concluded that the system's functionality has been successful overall. User acceptance test were conducted with the clinic's admin, and based on the test results, the system functions well and is acceptable to users. Usability testing yielded a score of 91.19%, indicating that the system is well-received by users.